Bistable electromagnetic generator based on buckled beams for vibration energy harvesting. (August 2014) - Cottone, Francesco; Basset, Philippe; Vocca, Helios; Gammaitoni, Luca; Bourouina, Tarik
Bistable piezoelectric generators have been demonstrated to outperform linear spring–mass–damper systems in terms of frequency bandwidth and harvested power from wideband vibrations. In this work, a nonlinear vibration energy harvester consisting of clamped–clamped buckled beams combined with a four-pole magnet across coil generator is investigated. By buckling the support beams, an elastic Duffing potential is provided so that the seismic mass can pass from being dynamically monostable to bistable. A theoretical model of the system is presented, and experimental tests are performed on a prototype. In the unbuckled state, the device exhibits higher maximum power at resonance than in the buckled, but, in general, no significant difference is noted in terms of average harvested power between monostable and bistable regimes under harmonic and band-limited stochastic vibrations. However, for an optimal acceleration level, the bistable configuration shows a factor of 2.5 times wider bandwidth and higher power outside from the natural resonance as compared with the monostable regime. It is also observed that the benefits of bistable dynamics mostly depend on the ratio between the characteristic cutoff frequency of the electrical circuit and the mechanical resonance.